Strategi Manajemen Perubahan Pola Pikir SDM Guna Menghadapi Persaingan Era Industri Pada Industri Pertanian - Raihan Sultani; Nuri Aslami (LPPM Universitas Labuhanbatu, 2026)
Organizational change management as a change in the whole organization or its parts and changes aimed at improving efficiency in terms of productivity, turnover, market competitiveness and internal harmonization which is a systematic process. Employee involvement is highly expected in change management, as they are the expected exporters of change.Â Change management in the HR sector is based on changeable thinking. Mindset is the most important and fundamental thing, because mindset is the root and foundation of employee behavior patterns. By laying the foundation for a better HR change, taking into account several factors of competitive change and internal HR factors that are behind the change of thinking, making HR changes can become a foundation for the company. maintain their presence on the competitive map of the industrial-era agricultural industry and provide the means for companies to achieve their goals.